Social Media Engagement and Influencer Personal Branding Relations Journal - Nur Lailatus Saidah; Qorina Salmaneta Setya Wulandari; Tri Wismiarsi (Jurnal Visionida, 2022)
The most excellent and straightforward method for creating a personal brand today is using social media to gain visibility in a particular industry or specialty. Personal branding can flourish in this environment because almost everyone is now online and will go there to discover more about someone’s personality and activities. This study aimed to determine the connection between some influencers’ branding and social media involvement. This study used a Google Form Survey to collect information from Indonesians born between 1965 and 2022 and familiar with Dedy Corbuzier and Cinta Laura as influencers with different personal branding strategies. The result shows that influencer social media engagement is affected by their branding. The independent variable (personal branding) tested influences the dependent variable (social media engagement). The implications of this research can be used for people working in a business where influencers’ specific criteria will affect their engagement.